EFFECT OF SEEDING DENSITY AND PLANTING TIME ON GROWTH AND YIELD ATTRIBUTES OF WHEAT - M. S. Baloch; I. T H. Shah; M. A. Nadim; M. I. Khan; A. A. Khakwani (Journal of Animal and Plant Sciences, 2010)
In rice-wheat cropping system, farmers usually use normal wheat seed (100 kg ha-1) even under late planting. The negative effect of late sowing may be compensated by the subsequent increase in seed quantity. In order to optimize seed rate and time of sowing of wheat variety Hashim-8, an experiment was conducted at the Agricultural Research Institute, Dera Ismail Khan on different sowing dates viz. October-25, November-10, November-25, December-10 and December-25 with seeding rates of 100, 125, 150, 175 and 200 kg ha-1. Data indicated higher number of tillers, spike length, plant height, 1000-grain weight and the grain yield with seed rate of 150 kg ha-1. Similarly, sowing wheat on October-25 and November-10 produced the highest number of tillers, spike length, plant height, 1000-grain weight and the grain yield, which subsequently decreased with successive sowing dates. On the basis of results obtained, it is concluded that wheat variety Hashim-8 should be sown between October-25 to November-10 with seed rate of 150 kg ha-1.
Keywords: Wheat; Triticum aestivum; sowing time; seed rate